Categorizing and assessing multi-campus universities in contemporary higher education. Issue 1 (2nd January 2017) - Pinheiro, Rómulo; Nordstrand Berg, Laila
Abstract : Multi-campus universities are not a new phenomenon per se, but they have become an increasing feature of contemporary higher education systems all over the world. In the case of Northern Europe, multi-campus universities are the consequence of contraction patterns resulting from overcapacity, fragmentation and rising competition. This paper has two main objectives. First, to take stock of the existing scientific literature on multi-campus universities and, on that basis, develop a novel conceptual framework for categorizing such systems, with focus on the level of autonomy and profile enjoyed by the individual campuses composing a given system or university. Second, we provide new empirical insights as a way of testing and contextualizing our conceptual model, by drawing upon a case university located in the Nordic countries.